2020
DOI: 10.1021/acsabm.0c00641
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Gold Nanoclusters Eradicate Escherichia coli Biofilms and Are Nontoxic by Oral Administration

Abstract: Escherichia coli biofilms are a major causative agent of many intestinal infections, and there is ongoing research aimed at E. coli biofilm eradication. Gold nanoclusters (AuNCs) conjugated with various surface ligands have been extensively investigated for antimicrobial properties and provide a potential solution. There is little known about their in vivo safety because current standards of nanosafety research involve incubation of AuNCs with cells in vitro to confirm biocompatibility. In addition to systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The latest studies have demonstrated that, in addition to the excellent physical and chemical properties, pep-AuNCs also exhibit unique intrinsic bioactivities and show good potential in the field of disease diagnosis and treatment [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. AuNCs have been reported to prevent and treat skin infections due to their antimicrobial activity [ 22 , 23 ]. However, their immunomodulatory properties and therapeutic potential in inflammatory skin diseases, such as contact dermatitis and psoriasis, are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The latest studies have demonstrated that, in addition to the excellent physical and chemical properties, pep-AuNCs also exhibit unique intrinsic bioactivities and show good potential in the field of disease diagnosis and treatment [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. AuNCs have been reported to prevent and treat skin infections due to their antimicrobial activity [ 22 , 23 ]. However, their immunomodulatory properties and therapeutic potential in inflammatory skin diseases, such as contact dermatitis and psoriasis, are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…When administered orally, AuNC@PEG‐OH and AuNC@PEG‐NH 2 demonstrated significant antibiofilm activity without causing notable changes in the blood parameters. [ 209 ]…”
Section: Bioresponses At the Organismal Scalementioning
confidence: 99%
“…12F). 75 Cao et al 91 reported a formulation of functionalized-gold nanoclusters by surface coating with hydroxyl (-OH) or amine (-NH 2 ) functionalized poly(ethylene glycol) in the presence of cell-penetration peptides (YGRKKRRQRRR-(b-ala) 3 -Cys-amide). The formulated nanoclusters (AuNCs@ PEG-OH or AuNCs@PEG-NH 2 ) were found to be effective against gastrointestinal biofilm infection by the causative pathogen, E. coli, demonstrating a remarkable biofilm removal activity at a minimum biofilm eradication concentration (MBEC) of 1 mg mL À1 .…”
Section: Nanotechnology Strategies For Biofilm Targeting and Eradicationmentioning
confidence: 99%
“…No toxicity effect was observed when further in vivo studies were conducted. 91 2.2.4 Metal and metal oxide NP formulations for preventing biofilms. One of the strategies for controlling biofilms is to prevent or inhibit their formation by using a variety of nanoparticles.…”
Section: Nanotechnology Strategies For Biofilm Targeting and Eradicationmentioning
confidence: 99%